Deviations of the SLM produced Lattice Structures and Their Influence on Mechanical properties - Vrána, Radek; Koutecký, Tomáš; Červinek, Ondřej; Zikmund, Tomáš; Pantělejev, Libor; Kaiser, Jozef; Koutný, Daniel (MDPI, 2022)
Selective laser melting (SLM) is an additive manufacturing technology suitable for producing cellular lattice structures using fine metal powder and a laser beam. However, the shape and dimensional deviations occur on the thin struts during manufacturing, influencing the mechanical properties of the structure. There are attempts in the literature to describe the actual shape of the struts’ geometry, however, on a smaller data sample only, and there is a lack of a universal FEA material model applicable to a wider range of lattice structure diameters. To describe the actual dimensions of the struts, a set of lattice structures, with diameters ranging from 0.6 to 3.0 mm, were manufactured using SLM. These samples were digitized using micro-computed tomography (CT) and fully analyzed for shape and dimensions. The results show large deviations in diameters of inscribed and circumscribed cylinders, indicating an elliptical shape of the struts. With increasing lattice structure diameter, the deviations decreased. In terms of the effect of the shape and dimensions on the mechanical properties, the Gaussian cylinder was found to describe struts in the diameter range of 1.5 to 3.0 mm sufficiently well. For smaller diameters, it is appropriate to represent the actual cross-section by an ellipse. The use of substitute ellipses, in combination with the compression test results, has resulted in FEA material model that can be used for the 0.6 to 3.0 mm struts’ diameter range. The model has fixed Young’s and tangential modules for these diameters and is controlled only by the yield strength parameter (YST).

Selective laser melting (SLM) is an additive manufacturing technology suitable for producing cellular lattice structures using fine metal powder and a laser beam. However, the shape and dimensional deviations occur on the thin struts during manufacturing, influencing the mechanical properties of the structure. There are attempts in the literature to describe the actual shape of the struts’ geometry, however, on a smaller data sample only, and there is a lack of a universal FEA material model applicable to a wider range of lattice structure diameters. To describe the actual dimensions of the struts, a set of lattice structures, with diameters ranging from 0.6 to 3.0 mm, were manufactured using SLM. These samples were digitized using micro-computed tomography (CT) and fully analyzed for shape and dimensions. The results show large deviations in diameters of inscribed and circumscribed cylinders, indicating an elliptical shape of the struts. With increasing lattice structure diameter, the deviations decreased. In terms of the effect of the shape and dimensions on the mechanical properties, the Gaussian cylinder was found to describe struts in the diameter range of 1.5 to 3.0 mm sufficiently well. For smaller diameters, it is appropriate to represent the actual cross-section by an ellipse. The use of substitute ellipses, in combination with the compression test results, has resulted in FEA material model that can be used for the 0.6 to 3.0 mm struts’ diameter range. The model has fixed Young’s and tangential modules for these diameters and is controlled only by the yield strength parameter (YST).
Deviations of the SLM produced Lattice Structures and Their Influence on Mechanical properties
Keywords: selective laser melting (SLM); lattice structure; shape and dimension analysis; computed tomography (CT); digitization; finite element analysis (FEA); selective laser melting (SLM); lattice structure; shape and dimension analysis; computed tomography (CT); digitization; finite element analysis (FEA)